تصور التكافل الاجتماعي: أنواعه وصوره البارزة في ضوء التعاليم الإسلامية - دراسة بحثية: Concept of Social Solidarity: Types and Prominent Forms in Light of Islamic Teachings - Research Study - Dr. Hafiz Hamid Ali Awan,; Madiha Mumtaz, (International Research Journal of Arabic and Islamic Studies, 2024)
Islam has the honor of being the last religion in the universe, it has the ability to be practiced by all human beings in all ages. The subject of Islam is man, respect for humanity, spiritual and material guidance are its main goals. To fulfill the physical needs of human beings, Allah Ta'ala has provided them with spiritual guidance through various prophets and heavenly books. It is a fact that human beings are not creatively equal in the pursuit of profit or in the disposal of profit. Therefore, the religion of Islam obliges the wealthy and the status class of the society to help the financially and practically weaker classes in this paper, keeping in mind the requirements of the present age, the importance and necessity of takaful is argued by Sharia Quran and Sunnah. It is clarified by Islam encourages the financial and intellectual guidance of different groups of society. In view of this importance, in this paper, the main types of takaful, academic takaful, political takaful, financial takaful, literary takaful and moral takaful (financial punishment for various crimes) have been explained in a very reasonable manner. This thesis consists of a case, three discussions and a conclusion. In these debates, the literal and terminological definition of takaful and the proof of financial takaful is proven from the Qur'an by Hazrat Zakariya (AS) sponsoring Hazrat Maryam (AS) and the best form of Takaful is the Islamic system of Zakat. So that they can live with respect and comfort. In this paper, waqf is presented as an excellent example of takaful, because in waqf, the property itself or its benefit is dedicated as a support for members of the society, and Muslim waqf from the beginning of Islam until now. They are continuing the process continuously, which no intelligent person can deny. In these papers, the justification and necessity of takaful has been succinctly embellished with logical arguments and simulations.